DISEASE CONTROL PURPLE BLOTCH (Alternaria porri L.) USING a PESTICIDEPLANT EXTRACT of BETEL LEAF ON the ONION PLANT (Allium ceppa L.) - Novia Mokalu; James B. Kaligis (Jurnal Agroekoteknologi Terapan, 2021)
Red onion is one of the vegetables that have important meaning for the people of the economic value and nutritional content. Onions contain calories, carbohydrates, fat, protein, dietary fiber, vitamins, and minerals. Red onion also contains the compound allicin and essential oils are bactericidal and fungicidal against bacteria and fungi. Demand for onion is good for consumption or seedlings in the country has increased. Every year almost always an increase in the production of red onion, but it has not been able to offset the increase in demand onion nationally along with the increasing population and the development of the processing industry. Keywords: red onion; betel leaf; extract. Abstrak                             Bawang merah merupakan salah satu komoditas sayuran  yang  mempunyai arti  penting  bagi  masyarakat  baik  dari  nilai  ekonomisnya  maupun   kandungan gizinya. Bawang merah mengandung kalori, karbohidrat, lemak, protein, serat makanan, vitamin, dan mineral. Bawang  merah mengandung  senyawa  allicin  dan  minyak  atsiri  yang   bersifat  bakterisida dan fungisida terhadap bakteri dan jamur. Permintaan  akan  bawang  merah  baik  untuk  konsumsi  ataupun bibit dalam negeri mengalami peningkatan. Setiap tahun hampir  selalu  terjadi  peningkatan produksi bawang merah, akan tetapi hal tersebut belum mampu mengimbangi peningkatan permintaan bawang merah secara nasional seiring dengan bertambahnya jumlah penduduk dan berkembangnya industri olahan. Kata kunci: bawang merah; daun sirih; ekstrak.